ANALISIS PENERAPAN PENDEKATAN SAINTIFIK PADA PENUGASAN DI BUKU TEKS BAHASA INDONESIA KELAS VII SMP BERDASARKAN KURIKULUM 2013 - Kurniasari, Fitri; Suhardi, Suhardi (Diksi, 2018)
Abstract(Title: Scientific Approach Application Analysis on Task in Indonesia Language Text Book for Seventh Grade Students Based on Curriculum 2013). This research aims to: (1) know the steps of "Scientific Approach" which are reflected on the tasks based on complete steps, (2) know the steps of "Scientific Approach" which are reflected on the tasks based on the sequence steps. The research design used in this research is content analysis. The main  instrument in this research is human instrument. The research data is collected with "simak" method with tecqnique "baca" and "catat". The data analysis is done using distributional method with tecqnique "pemilahan" based on catagory. The research reveals two findings. First, based on the complete steps, there found complete and incomplete task step. Second, based on sequence steps, there are sequence task and not sequence task.Keyword: task, text book, scientific approach, Curriculum 2013